Evaluation of dietary supplementation of ammonium sulphate on in vitro gas production and rumen fermentation characteristics of WAD ewes (2016)
Ammonium sulphate, a chemical compound was utilized to evaluate its potential through in vitro gas production technique and rumen fermentation characteristics as a rumen stimulator and mitigates methane gas. Four experimental diets were formulated with ammonium sulphate (AS) included at varying levels: T1 (control/0% AS), T2 (control diet + 0.25% AS), T3 (control diet + 0.50% AS) and T4 (control diet + 0.75% AS). Rumen fluid was collected from the ewes, sixteen in number and weighing 24 kg averagely, using suction tube method to evaluate in vitro gas production, determine microbial population and rumen fermentation characteristics. Gas production was determined over a 96 hour period. Other data collected included organic matter digestibility (OMD%), short Chain Fatty Acids (SCFA μml), Metabolisable Energy (ME MJ/KJ DM), Degradability (D%), Volatile Fatty Acids (VFA), rumen pH, temperature and ammonia nitrogen (AN). Results showed no significant differences (p>0.05) for in vitro gas production profiles (i.e. total gas, OMD, ME, SCFA). However, as inclusion increased it stimulated the parameters measured to be numerically higher than control. Methane gas was highest for control diet (4 ml/200 mg DM) while T2 recorded the least (2 ml/200 mg DM). Degradability increased as the inclusion level of AS increased. Control diet was the lowest (32%) while T4 had the highest (45%). The rumen fermentation characteristics showed significant (p<0.05) differences for all the parameters measured except rumen temperature. Animals on T4 diet recorded the highest (p<0.05) pH value (6.85) while those on T2 diet had the least (6.53). Animals on Control diet recorded the highest values (p<0.05) for AN and acetic acid (100.40 mg/l and 8.98 mol/100L) while the least values were observed in animals on T2 diet (AN) and those on T4 (acetic acid). Increase inclusion of AS caused a decrease in acetic acid. Rumen bacteria was highest (p<0.05) in animals on T4 (1.40 x 10(6)cfu/mm(3)) and lowest in those on T3 (0.65 x 10(6)cfu/mm(3)). For fungi and protozoa, animals on T4 and T2 diets were higher (p<0.05) respectively than those on Control diet (1.15 and 1.09 x 10(6)cfu/mm(3) compared to 1.10 and 0.85 x 10(6)cfu/mm(3) respectively). Supplementation of AS has been validated by this study, with a 0.75% inclusion level resulting in lowest methane gas, and higher ME, SCFA, pH, bacteria and fungi and may be recommended for ruminant feeding.